Nicotinamide adenine dinucleotide metabolism and arterial stiffness after long-term nicotinamide mononucleotide supplementation: a randomized, double-blind, placebo-controlled trial - Takeshi Katayoshi; Sachi Uehata; Noe Nakashima; Takahisa Nakajo; Natsuko Kitajima; Masakatsu Kageyama; Kentaro Tsuji-Naito (Scientific Reports, 2023)
Abstract Many animal studies have shown that oral administration of the nicotinamide adenine dinucleotide (NAD+) precursor nicotinamide mononucleotide (NMN) prevents the reduction of NAD+ levels in organs and tissues, helping alleviate aging-related diseases. However, there are very few clinical reports of NMN supplementation in humans. Thus, this study aimed to investigate the influence of a 12-week NMN oral supplementation on biochemical and metabolic health parameters. A 12-week randomized, double-blind, placebo-controlled, parallel-group clinical trial was conducted. A total of 36 healthy middle-aged participants received one capsule of either 125 mg NMN or placebo twice a day. Among the NAD+ metabolites, the levels of nicotinamide in the serum were significantly higher in the NMN intake group than in the placebo group. Pulse wave velocity values indicating arterial stiffness tended to decrease in the NMN intake group. However, no significant difference was found between the two groups. Long-term NMN supplementation at 250 mg/day was well tolerated and did not cause adverse events. NMN safely and effectively elevated NAD+ metabolism in healthy middle-aged adults. Additionally, NMN supplementation showed potential in alleviating arterial stiffness.